Synthesis of 4,7-dibromo-9H-carbazole and its N-alkylation under Microwave Activation Conditions in a Flow-type Microwave Reactor - Vetrova, Anastassiya; Khrustalev, Dmitriy; Yedrissov, Azamat; Khrustaleva, Anastassiya (The 8th International Conference on Nanomaterials and Advanced Energy Storage Systems; Nazarbayev University; National Laboratory Astana; Institute of Batteries, 2020)
The study is devoted to one of the most popular and expensive building blocks synthesis design (4) in a microwave flow reactor, which are used in the Photovoltaic Polymers synthesis. Replacing the bath-type reactor, in which we studied this reaction before, [1,2] with a flow-type reactor opens up the possibility for industrial production (4) under microwave activation conditions. The use of a microwave flow reactor allowed to avoid a reducing of the microwave synthesis efficiency by increasing the amount of reagents and obtaining a bigger amount of product (2), (3), (4).